The Effect of Additional Fruit Eggplant (Solanum betaceum cav.) Juice on the Characteristics of Black Tea (Camelia sinensis) Beverage - Diana Sylvi; Fauzan Azima; Sandonella Anggini (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2021)
This study aims to determine the effect of adding Dutch eggplant juice on the characteristics of black tea drinks. This study used a completely randomized design (CRD) with 5 treatments and 3 replications. The data was analyzed statistically with the F test, if it was significantly different, it was continued with Duncan's new Multiple Range Test (DNMRT) at the level of 5%. The addition of Dutch eggplant juice was 6%, 8%, 10%, 12%, 14%. This study showed the effect of adding Dutch eggplant juice to vitamin C, PH, antioxidants, polyphenols, flavonoids, alkaloids, tannins, saponins and sensory analysis (color, aroma and taste). The best product was the product with treatment E (addition of 14% Dutch eggplant extract) with antioxidant characteristics of 77.67%, polyphenols 393.37 mg GAE/g, flavonoids 296.83 mg QE/g, vitamin C 168.96 mg/100g, pH 4, alkaloid (+), tannin (+), saponin (+), color 3.05, aroma 3.90 and taste 3.75.